WORKSHOP FOR INDONESIAN LANGUAGE TEACHERS OF JUNIOR HIGH SCHOOL LEVEL IN THE DISTRICT OF JALAN CAGAK KAB. SUBANG ON THE USE OF GOOD AND APPROPRIATE INDONESIAN LANGUAGE TO IMPROVE THE ETHICS OF KARIMAH - Dedi Junaedi; Hendra Husnussalam; tamtam Kamaluddin; Sahliah Sahliah (IKIP Siliwangi, 2019)
Language is something that is very important because by using language a person can communicate and adapt, and based on good and correct speech, he/she becomes an individual who has the morality of karimah. A society can be classified as having good characters if they use polite and appropriate language in daily life or various opportunities. In line with the goals and objectives of national development, national education is directed at efforts to improve the quality of Indonesian people. Humans with faith and devoted to God Almighty are those with virtuous character, personality, disciplined, hardworking, tough, responsible, independent, intelligent and skilled, and healthy physical and physical. In this connection, teachers, as the spearhead, are good role model in the eyes of their students. The teachers are those who are followed and imitated by students. Even thousands of teachers teach in various schools or formal and informal institutions, teachers are scattered in rural and urban areas throughout Indonesia. The teacher is one of the centers for the development of mental mentality in societies with different sociocultural stratification. Teachers can produce sociocultural and civilizational stratification in the sense of forming good and noble character of moral character, thus there must be coaching in every aspect in order to create a synergy between good and right language with moral character to the high school teachers in the district of Kec. Jalan Cagak Kab. Subang.